Access with success: the reaching for excellence and achievement program at the University of the Witwatersrand - Ndaba, Mthobisi (My University, 2017)
Since the debut of democracy, there has been an increase in the number of historically marginalised Black students in South Africa’s higher education institutions. However, this has not been accompanied by a corresponding success rate. Higher education’s response to this success crisis has largely been academic development programs. While extensive research has been done on academic development programs, more especially quantitative research in disciplines like maths, natural sciences, and economics, not much qualitative research has been done on extracurricular academic development programs in the humanities and the social sciences. In this study, I explore the role of the Reaching for Excellence and Achievement Program (REAP) in students’ journeys graduation. REAP is an extracurricular academic development program at the University of the Witwatersrand. The findings show that students from disadvantaged backgrounds are not a homogeneous group and that this influences the types of challenges that they encounter at university. They show that REAP played a significant role in facilitating these students’ progress to graduation. They also reveal that academic development programs by themselves are not enough to address the success crisis facing students from disadvantaged backgrounds because the root causes of some of the challenges they encounter can only be addressed at a structural level. Based on the lessons learned from the findings of this study, I make recommendations for future academic development programming. Keywords: Access, Success, Academic Development, Under-preparedness, Educational Inequality, Higher Education
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Sociology, 2017
Keywords: College student development programs--South Africa; Counseling in higher education--South Africa; Academic achievement--South Africa